Analysis of Junior High School Students’ Scientific Creativity Profiles in Terms of Gender Differences and Cognitive Levels - Siska Ayu Nirmala; Joni Rokhmat; Agus Ramdani; Aa Sukarso; Hisbullah Als Mustofa (International Journal of Contextual Science Education, 2025)
Creative thinking skills are among the essential competencies students must possess to face global challenges in the 21st century. This study aims to analyze the profile of students’ scientific creativity in terms of gender differences and cognitive level. A descriptive quantitative method was employed, involving 36 junior high school students. The instruments used included a scientific creativity test based on the Hu & Adey model and documentation of students’ science grades to determine their cognitive levels. Data analysis consisted of both descriptive and inferential approaches. Descriptive analysis was used to examine the characteristics of the data, including maximum score, minimum score, and average student score. Based on the scientific creativity scores, students were categorized into three groups: creative, moderately creative, and less creative. Inferential analysis involved an independent sample t-test to examine gender differences in scientific creativity and a Pearson correlation test to investigate the relationship between scientific creativity and cognitive level. The results showed that students' scientific creativity fell into the moderately creative category, with female students achieving higher average scores than male students, particularly in the dimensions of fluency and originality. The t-test revealed a significant difference in scientific creativity between male and female students. Students with higher cognitive levels tended to have better scientific creativity scores, although the Pearson correlation test showed that the relationship between cognitive level and scientific creativity was not statistically significant. In conclusion, female students demonstrated higher levels of scientific creativity than their male counterparts, and cognitive level did not show a significant correlation with students’ scientific creativity.